2023
DOI: 10.1109/joe.2022.3220330
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric Reconstruction From Sidescan Sonar With Deep Neural Networks

Abstract: He is currently a Researcher with the Swedish Maritime Robotics project at KTH. His research interests include robotic sensing and mapping, with a focus on probabilistic reasoning and inference. Most of his recent work has been on applications of specialized neural networks to underwater sonar data. In addition, he is interested in system integration for robust and long-term robotic deployments.John Folkesson (Senior Member, IEEE) received the B.A. degree in physics from Queens College, City University of New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They showed that convergence can be improved by gradually increasing the resolution of the predicted bathymetry. Recently, data-driven approaches [5], [6] using CNNs have been proposed to learn the missing elevation directly from SSS images in a supervised-learning fashion. However, the "ground truth" bathymetry is needed for creating a training set, which is not always practical underwater.…”
Section: Sss Bathymetry Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…They showed that convergence can be improved by gradually increasing the resolution of the predicted bathymetry. Recently, data-driven approaches [5], [6] using CNNs have been proposed to learn the missing elevation directly from SSS images in a supervised-learning fashion. However, the "ground truth" bathymetry is needed for creating a training set, which is not always practical underwater.…”
Section: Sss Bathymetry Reconstructionmentioning
confidence: 99%
“…Similarly, for the shadows in the data, the gradient descent procedure would find a intersection between the arc and the seafloor, but the found intersection is occluded. Inspired by [9], [10], we propose to sample a few points along the ray backwards, starting from the intersection and compute the accumulated transmittance at the intersection T (p(ϕ * )) = exp (− r s 0 ρ(u)du), which is used to indicate if p(ϕ * ) is occluded. Here, the particle density ρ is computed as in [9], [10].…”
Section: σSmentioning
confidence: 99%
See 2 more Smart Citations
“…A complete study of our planet’s topography is an extremely challenging task, since almost three-quarters of the planet’s surface is covered by water, and the depth in some areas can reach several kilometers [ 6 ]. At present, modeling of the seafloor surface can be performed based on measuring the depth of a body of water, resulting in a corresponding bathymetric dataset [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%